Keabsahaan Talak Di Luar Pengadilan Agama Perspektif Hukum Islam Dan Hukum Positif - Azhari, Doni Azhari; Asmuni, Asmuni (Berasan: Journal of Islamic Civil Law, 2024)
This paper aims to strengthen the opinion or concept of the validity of a law relating to triple talaq out of court with the perspective of Islamic law and positive law. This paper is the result of qualitative research on a number of data sources (works); books and articles discussing and/or research results regarding the legal validity of triple talaq outside the religious courts. To see the role and/or function of writing, Teubner's theory of legal certainty is used, the law that can satisfy all parties is responsive law and responsive law is only born if there is democratization of legislation. Without democracy (community participation) in the legislative process the result will never give birth to an independent law. The interests of the community are neglected because the law is independent because its meanings refer to itself (justice, certainty, benefit). Law Number 1 of 1974, the pronouncement of divorce must be done in front of the court, otherwise the divorce is not recognized by state law. And the husband and wife are still bound by state law even though according to Islamic law they are no longer husband and wife.